Gut microbiota is not modified by Randomized, Double-blind, Placebo-controlled Trial of VSL#3 in Diarrhea-predominant Irritable Bowel Syndrome - Michail, Sonia (2011)
Irritable Bowel Syndrome (IBS) is a common condition that negatively impacts the quality of life for many individuals. The exact etiology of this disorder is largely unknown; however, emerging studies suggest that the gut microbiota is a contributing factor. Several clinical trials show that probiotics, such as VSL#3, can have a favorable effect on IBS. This double-blind, randomized placebo-controlled study has been conducted in diarrhea-predominant IBS subjects in order to investigate the effect of VSL#3 on the fecal microbiota. The bacterial composition of the fecal microbiota was investigated using high-throughput microarray technology to detect 16S RNA. Twenty four subjects were randomized to receive VSL#3 or placebo for 8 weeks. IBS symptoms were monitored using GSRS and quality of life questionnaires. A favorable change in Satiety subscale was noted in the VSL #3 groups. However, the consumption of the probiotic did not change the gut microbiota. There were no adverse events or any safety concerns encountered during this study. To summarize, the use of VSL#3 in this pilot study was safe and showed improvement in specific GSRS-IBS scores in diarrhea-predominant IBS subjects. The gut microbiota was not affected by VSL#3 consumption suggesting that the mechanism of action is not directly linked to the microbiota.